Lyme disease in Canada: Focus on children - Onyett, Heather (Pulsus Group Inc, 2014)
Lyme disease, the most common tick-borne infection in Canada and much of the United States, is caused by the bacteria Borrelia burgdorferi. Peak incidence for Lyme disease is among children five to nine years of age and older adults (55 to 59 years of age). The bacteria are transmitted through the bite of infected black-legged ticks of the Ixodes species. The primary hosts of black-legged ticks are mice and other rodents, small mammals, birds (which are reservoirs for B burgdorferi) and white-tailed deer. Geographical distribution of Ixodes ticks is expanding in Canada and an increasing number of cases of Lyme disease are being reported. The present practice point reviews the epidemiology, clinical presentation, diagnosis, management and prevention of Lyme disease, with a focus on children.